2023
DOI: 10.2478/pjmpe-2023-0008
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of virtual rhinomanometry

Abstract: Introduction: This paper describes the results of research aimed at developing a method of otolaryngological diagnosis based on computational fluid dynamics, which has been called Virtual Rhinomanometry. Material and methods: Laboratory studies of airflows through a 3D printed model of nasal cavities based on computed tomography image analysis have been performed. The CFD results have been compared with those of an examination of airflow through nasal cavities (rhinomanometry)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“… m 2 /s and m 2 /s are the mass diffusion coefficient of the boundary layer and mucous membrane [ 14 ]. The thickness of the boundary layer and the mucous membrane layer thickness is mm and mm, respectively [ 34 ].…”
Section: Numerical Simulation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… m 2 /s and m 2 /s are the mass diffusion coefficient of the boundary layer and mucous membrane [ 14 ]. The thickness of the boundary layer and the mucous membrane layer thickness is mm and mm, respectively [ 34 ].…”
Section: Numerical Simulation Methodsmentioning
confidence: 99%
“…Numerical analysis has been used in various studies such as airflow diagnostics in patients with sleep apnoea, deposition fraction, and drug delivery efficiency [ 12 , 13 ]. Recent research has confirmed that the use of numerical modelling to analyse airflow through the nasal cavity (virtual rhinomanometry) can be considered a reliable method [ 14 ]. Many studies have shown that simulations and numerical modelling, particularly numerical fluid dynamics (CFD), are mature and reliable enough to be treated as part of personalized medicine.…”
Section: Introductionmentioning
confidence: 99%